Cognitive function in Indonesian children with type 1 diabetes mellitus - Ulfa, Marselya; Aditiawati, Aditiawati; Hasanah, Yulisnawati; Dhaini, Shafri; Bakrie, Achirul; Indra, Raden Muhammad (Paediatrica Indonesiana, 2024)
Background Children with type 1 diabetes mellitus (T1DM) are at risk of cognitive impairment. While the pathophysiology is still unclear, cognitive impairment in children with T1DM can result in significant negative effects on quality of life. Objective to evaluate the cognitive function of Indonesian children with T1DM and its association with glycemic control and to identify factors affecting cognitive function in children with T1DM. Methods The cognitive function of children aged 6 years or older with T1DM was measured using the Wechsler Intelligence Scale for Children-Revised (WISC-R). We analyzed for potential associations between cognitive function and glycemic control based on mean HbA1c levels and other factors, such as the age of onset, duration of illness, and maternal educational attainment. We also identified failure to achieve age-appropriate results on any of the WISC-R subtests (cognitive impairment) and associated factors. Results A total of 46 subjects were included in this study, with a mean age of 12.8 (SD 3.4) years. There were 27 (58.7%) girls and 19 (41.3%) boys. Subjects’ mean full-scale IQ (FSIQ) was 91.35 (SD 11.43). A moderate negative correlation was found between FSIQ and mean HbA1c levels (r=-0.43; P<0.01). Children with mothers who had university degrees had significantly higher IQs (mean difference 7.39; 95%CI 3.10 to 13.66; P=0.02) than those with mothers without degrees. Failure of any WISC-R subtest was noted in 34 subjects, consisting of 17 verbal, 1 performance, and 34 verbal and performance subtests. A higher proportion of those with cognitive impairment had mean HbA1c >10%. However, compared to those with mean HbA1c ?10, the difference did not reach a statistical significance (OR 5.0; 95%CI 0.95 to 26.31; P=0.50) Conclusion Glycemic control and maternal educational attainment are associated with cognitive function in Indonesian children with T1DM. Poor glycemic control is also associated with a higher risk of cognitive impairment.